(3eQTOI GdeTJZdjf aj CMcGe Gdfhf GdSGcfI hGdJfhjfs - (3eMeO fGUQ GdOjf GdWHdGhj GdTGaYjs ((3SdGe Hf Ydj Hf YWjI GdeGdcj s)
(3ChdgG (B:s
(3hHYO agPg ebOeI LejdI eTJedI Ydi fcJ LdjdI aj CdaGX bdjdI, SejJgG eQTOI GdeTJZdjf s
(3BNQgG (B:s
(3hgh fHPI jSjQI HGdfSHI Edi eG aj cJH GdbQGA HeG dGZfi ddbGQF hdLejY GdeSedjf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B468s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs